Modelling of 14NM gate length La2O3-based n-type MOSFET - Mah S.K.; Ahmad I.; Ker P.J.; Noor Faizah Z.A. (Universiti Teknikal Malaysia Melaka, 2023)
Gate length shrinkage is still the widely used method in transistor downsizing. In view of this, the downsizing of Equivalent Oxide Thickness (EOT) is also of high importance as it is the main focus in the process. Therefore, various studies on Metal Oxide Semiconductor Field Effect Transistors (MOSFETs) fabricated from high-k dielectric and metal gate have been reported till today. In this paper, a 14nm silicon based n-type MOSFET was virtually fabricated using Lanthanum Oxide (La2O3) on Titanium Silicide (TiSi2). ATHENA and ATLAS modules from SILVACO were used for process and device simulation respectively. The results from this work show that the threshold voltage, VTH, on-current, ION and off-current, IOFF are 0.208397 V, 4.80048 x 10-5 A/?m and 1.00402 x 10-7 A/?m respectively. Furthermore, it is demonstrated that the development of high-k/metal gate MOSFET is a promising prospect for high performance nanoscale transistors.